The Inclusive Classroom : A new approach to differentiation. - Sobel, Daniel (Bloomsbury Education, 2021)
Effective inclusion in the classroom shouldn't be a burden; it should be the most rewarding aspect of a teacher's role. In this innovative guide to supporting the most vulnerable students, experts Daniel Sobel and Sara Alston help teachers understand the barriers to children's learning. Emphasising the importance of meeting needs rather than focusing on diagnosis, they provide proven differentiation methods that improve learning for the whole class, while reducing stress and saving time for the teacher.